The model of online health information-seeking behavior among older adults - Sara Pourrazavi; Shahrzad Bazargan-Hejazi (BioSocial Health Journal)
Introduction: Although age-related changes have caused more and different information needs in the older adults, their participation in online search is low. This study aimed to explore the process of online health information-seeking (OHIS) in the older adults. Methods: The current qualitative study was conducted through applying a grounded theory approach using Corbin and Strauss method in Tabriz from 2018 to 2019. Adopting a purposive and theoretical sampling method 19 older persons, 2 members of their family, a doctor, a psychologist, 4 gerontologists, and a health education specialist participated in this study. In-depth individual interviews were used as the main method of data collection. Results: This study indicated that the core phenomenon in the OHIS process was "struggling for healthy survival". Therefore, older people tried to identify and choose strategies to relying on yourself in taking care of their health. Avoidance of dependence as a contextual factor influenced their choice. Finally, this complex process led to OHIS. Conclusion: This study provides important insights for healthcare professionals and introduces some strategic implications for improving older people’s access to appropriate health information. The OHIS theory presented in this study is a potentially valuable tool for policymakers to take measures to support older people in their self-care.